Desenvolvimento de coletor solar construído com material proveniente de resíduo sólido de indústrias gráficas - Rebelato, Danielly Letícia (2019)
Environmental degradation is a major problem in today's society and it’s necessary to seek alternatives to mitigate man-made impacts on the environment through sustainable, viable solutions that see the reuse of materials that are usually discarded, contaminating and / or polluting the environment. This context, this work has as main objective, to develop a solar collector with materials of low cost and recyclable. The proposed collector differs from other alternative collectors by being constructed with the reuse of aluminum sheets, derived from compensated, used in several graphic industries. In this way, these chapters were adapted in a solar collector to function like fins, at the same time that they were associated to PVC pipes, forming a system of capture of high efficiency. Analysis of the feasibility of the proposed solar collector, were extra the experiences, divided into two categories. In the experiment without breath and without experiment with fin, the tests were in baptized regime and without complete experiment, the test was passive in continuous regime. Comparing the results of the experiment with and without fin, it was possible to verify if there is a source of water to reach a higher temperature. No complete experiment, published in all its studied aspects, had a thermal gain during the day. As a result of the console, it was found that the system increased 1 ° C at the reservoir temperature from the initial temperature. In this way, the experiments indicated a feasibility of using the proposed solar collector as a way of reducing the consumption of electric energy for water heating. In a general context, the study had a new alternative of recyclable material for use in low-cost heating systems, thus promoting sustainable development. The benefits and implementation of the survey should be widely disseminated, especially among the low-income population.